WEB SPACES FOR A DIGITAL VISUAL SEMIOTICS - Reyes, Everardo (Laboratório Editorial FCL-UNESP, 2016)
In this paper, we consider the web as a pertinent environment for studying visual semiotics. We observe the application of recent developments in information processing and data visualization on the web. Indeed, the web has become a solid platform to interactive space design. At first glance, we can identify these spaces to website types and genres, but we believe it is also possible to create original spaces directly inspired on semiotic methodologies and practices. Moreover, such spaces have been proved complex because they serve as graphical interface to manipulate the content, but also as the content itself. At the end of the paper, we stress the importance of considering a “digital semiotics” line, for instance, a semiotic approach that employs digital technologies as object of study, enunciation space, and environment to create new graphical interfaces grounded on visual semiotics.